2016
DOI: 10.1016/j.cyto.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the development and regulation of T follicular helper cells

Abstract: T follicular helper (Tfh) cells are specialized subset of T helper (Th) cells necessary for germinal center reaction, affinity maturation and the differentiation of germinal center B cells to antibody-producing plasma B cells and memory B cells. The differentiation of Tfh cells is a multistage, multifactorial process involving a variety of cytokines, surface molecules and transcription factors. While Tfh cells are critical components of protective immune responses against pathogens, regulation of these cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 139 publications
(243 reference statements)
0
21
0
Order By: Relevance
“…3 The differentiation of naive CD4 + T cells toward Tfh cells is a multistep programme in which cell-to-cell contacts as well as cytokine environment are critical. 4,5 Mature antigen-presenting cells migrate from the periphery to the lymphoid tissues to activate their cognate naive CD4 + T cells in the T-cell zone. Upon activation, CD4 + T cells up-regulate CXCR5 and migrate to the B-cell zone where they will encounter cognate B cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 The differentiation of naive CD4 + T cells toward Tfh cells is a multistep programme in which cell-to-cell contacts as well as cytokine environment are critical. 4,5 Mature antigen-presenting cells migrate from the periphery to the lymphoid tissues to activate their cognate naive CD4 + T cells in the T-cell zone. Upon activation, CD4 + T cells up-regulate CXCR5 and migrate to the B-cell zone where they will encounter cognate B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several cytokines, such as interleukin-6 (IL-6), IL-21 and IL-12 have been involved in the development of Tfh cells. 4,6 After considering the recent data on Tfh cell dynamics in HIV/simian immunodeficiency virus (SIV)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T fh cells synthesize characteristic cytokines (such as interleukin [IL]-21 and IL-4) that facilitate antibody production by and class-switch recombination events in B-cells. Over recent years, it has been shown that the expression of typical transcription factors (such as Bcl-6 and c-MAF)along with their mutual regulationis of crucial significance for the initial differentiation of, and essential functions thereafter, of T fh cells (Crotty 2014;Qi et al 2014;Butler and Kulu 2015;Jogdand et al 2016;Wali et al 2016;Qin et al 2018).…”
Section: Introductionmentioning
confidence: 99%